Casamento legal e divórcio segundo diferenciais de idade entre cônjuges: Brasil, 1991 e 2000 - Mariana Loredo Mayer Soares (2013)
This work aims to find the probabilities of legal marriage and divorce by age differential between spouses and by age group, for both sexes, for the years 1991 and 2000, data from the Civil Registration and Brazilians Censuses. The marriage is a very important feature for demographic studies and public policy planning, and the main contribution of this work is the discrimination of the transition probabilities of marital status by differential age of the spouses.